Exercise and Dietary-Protein as a Countermeasure to Skeletal Muscle Weakness: Liverpool Hope University – Sarcopenia Aging Trial (LHU-SAT) - Kirk, Ben; Mooney, Kate; Amirabdollahian, Farzad; Khaiyat, Omid (Frontiers in Physiology, 2019)
Objective To investigate the effects of a 16-week concurrent exercise regimen [resistance exercise (RE) + functional exercise (FE)] in combination with, or without, a leucine-enriched whey protein isolate supplement on muscle strength, physical functioning, aerobic capacity, and cardiometabolic health in older adults (≥60 years). Physical activity levels were also evaluated 6 months post-cessation of the intervention. Methods Forty-six, community-dwelling, previously untrained males, and females [age: 68 ± 5 years (mean ± SD); BMI: 27.8 ± 6.2 kg/m2] who completed the trial were initially randomized to one of two independent arms [Exercise n = 24 (E); Exercise+Protein n = 22 (EP)]. Both arms completed 16 weeks of RE (performed to fatigue) (2 times/week) with FE (1 time/week) on non-consecutive days. Additionally, EP were administered a leucine-enriched whey protein supplement (3 times/day) for 16 weeks based on individual body-weight (1.5 g/kg/day). Results As a result of dietary supplementation, protein intake increased in EP (∼1.2 ± 0.4 to 1.5 ± 0.7 g/kg/day) during the intervention. Maximal strength (1RM) values for leg press (E: +39 ± 7 kg, p = 0.006; EP: +63 ± 7 kg, p < 0.001), chest press (E: +22 ± 4 kg, p < 0.001; EP: +21 ± 6 kg, p < 0.001), and bicep curl (E: +7 ± 0 kg, p = 0.002; EP: +6 ± 1 kg, p = 0.008) significantly increased in E and EP respectively, with no differences between arms (p > 0.05). Physical functioning in the obstacle course (E: -5.1 ± 6.8 s, p < 0.001; EP: -2.8 ± 0.8 s, p < 0.001) and short-physical performance battery scores (E: +0.5 ± 0.5, p = <0.001; EP: +0.4 ± 0.5, p = 0.038), and aerobic capacity in the 6-min walk test (E: +37 ± 24 m, p = 0.014; EP: +36 ± 3 m, p = 0.005) improved in E and EP respectively, with no differences between arms (p > 0.05). No significant change was observed for markers of cardiometabolic health (glycaemic control or blood pressure) (p > 0.05). At follow-up, 86% of older adults reported to performing physical activity ≥1 per week. Of those, 61% were still participating in strength- and cardiovascular- based exercise. Conclusion Concurrent exercise (RE + FE) offers a potent method to combat age-related muscle weakness, and our results suggest a high proportion of older adults may continue to exercise unsupervised. However, leucine-enriched whey protein isolate supplementation did not confer any additional benefit in those already consuming ample amounts of dietary protein at trial enrolment. Future trials should utilize a whole-foods approach and investigate the effects in frail and non-frail older adults habitually consuming the RDA of protein, to assess if a higher intake of protein is needed to delay the onset of muscle weakness. Trial Registration Clinicaltrials.gov Identifier: NCT02912130.